Estabelecimento de classes de estímulos equivalentes com estímulos significativos: investigando a atitude racial preconceituosa - Mizael, Táhcita Medrado (Universidade Federal de São Carlos, 2015)
Research upon attitude s formation and change using the stimulus equivalence paradigm has shown, at the same time, a potential for the formation of new classes, and a difficulty with respect to teaching new relationships when the stimuli used are familiar and socially loaded. As racial prejudice is a problem worldwide, and stimulus equivalence paradigm has proven to be useful when studying attitude s formation and change, the aim of this study was to verify, from a systematic replication, if teaching new relations to children who showed a negative racial bias towards black people could revert the pre-existing classes. The level of 54 children s bias was assessed by the Self-Assessment Manikin (SAM), an instrument that measures the affective experience of individuals on pictures or events. The 22 participants who had attributed to black people s pictures lower levels of pleasure compared to white people s pictures also performed a second test aimed to confirm the bias shown. The 13 participants whose negative bias towards black people was confirmed were trained to match indirectly black people s pictures with positive attributes in a matching-to-sample task. Two experimenters, a black and a white one conducted the research with different children, to evaluate possible differences in the participants performance. The performances of these children were compared in two conditions: using simultaneous or delayed matching-to-sample, analyzing 1) How many children formed the expected equivalence classes; 2) in which of the two conditions the results were more robust; and 3) if the presence of white faces as a third comparison-stimuli in a modified equivalence test caused changes in the previous responses given by the participants who responded in accord with stimulus equivalence. Two instruments, a self-report and a implicit measure were used as complementary measures of transfer of functions, to evaluate the meaning of the stimuli. Results showed no differences between delayed and simultaneous matching-to-sample, or between the experimenters in the formation of the equivalence classes. All 13 participants who demonstrated a negative racial bias showed formation of the equivalence classes experimentally planned. Of those 13 children, nine have maintained their responses on the modified equivalence test, and the group data showed transfer of function, evidenced by SAM. Although there was a statistically significant difference between the pleasure levels of white and black faces before the class formation, post-test data revealed no statistically significant differences; this was also confirmed by the results of another instrument, called Implicit Relational Assessment Procedure (IRAP). Future research should recruit a larger number of participants and systematically change variables such as the use of mixed training of trained relations and the review of baseline relations, in order to identify which of them may be responsible for the positive results of equivalence.
Establishment of stimulus equivalence classes using meaningful stimuli: investigating racial prejudiced attitudes
Keywords: Aprendizagem; Equivalência de estímulos; Racismo; Atitude (Psicologia) - Mudança; Classes de estímulos equivalentes; Preconceito racial; Mudança de atitude; Stimulus equivalence; Racial prejudice; Attitude change; Socially loaded stimuli; Reorganization of stimulus classes; CIENCIAS HUMANAS::PSICOLOGIA